Design and development of multiphase buck converters for voltage regulator modules - Mini Puthenpurakkal Varghese; Ashwathnarayana Manjunatha; Thazhathu Veedu Snehaprabha (Institute of Advanced Engineering and Science, 2022)
Modern microprocessors in high-power applications require a low input voltage and a high input current, necessitating the use of multiphase buck converters. As per microprocessor computing complexity, the power requirements of the switching converter will also be more important and will be increasing as per load demand. Previous studies introduced some methods to achieve the advantages associated with multiphase regulators. This paper presents an effective closed closed-loop control scheme for multiphase buck converters that reduces ripple and improves transient response. It is suitable for applications that require regulated output voltage with effectively reduced ripple. The analysis began with a simulation of the entire design using the OrCAD tool, followed by the construction of a hardware setup. Experiments on a 200 Khz, 9 V, 12 A, 2-phase buck voltage regulator were conducted and the proposed experiment found to be useful.